Alterações bucais e parâmetros salivares em pacientes portadores de doença renal crônica em hemodiálise - Nascimento, Maria auxiliadora Gomes do (2014)
The Chronic Kidney Disease (CKD) is characterized by progressive and irreversible loss of kidney function. The impact of this disease on oral health also presents controversial results. The aim of this study was to determine the oral health status and sialometrics parameters and sialochemical of CKD patients on hemodialysis. A cross-sectional, descriptive epidemiological study, with a sample of 74 individuals undergoing dialysis treatment. Held oral history and clinical examination, as well as oral indexes were applied: DMFT (decayed tooth, Lost and plugged), CPI (Community Periodontal Index), OHI-S (Simplified Oral Hygiene Index) and ISG (Index of gingival bleeding). Sialometry was held in resting and stimulated and given the salivary urea rate. Data were analyzed using SPSS v.s. 20.0, being held descriptive analysis and applied Fisher tests, Wilcoxon, Tukey, ANOVA and Spearman correlation. Of the total sample, 64.9% were male. The average age was 50.7 ± 14.8 years. Most had some kind of systemic change (79.7%) and hypertension (66.2%) and diabetes (27%) the most prevalent. All patients were using drugs, and the antianemics, the recalcificantes and antihypertensive the most frequent. In 36.5% some oral lesion was diagnosed in 29.7% and 31.1% xerostomia disgeusias. The DMFT average was 20.49 + 8.68; the SOHI was satisfactory in 73%; CPI in the presence of dental calculus occurred in 52.7%; In 78.4% the ISG reflected lower risk of caries and periodontal disease activity downtown. The average salivary flow at rest (FSR) was 0.20 ± 0.18 ml / min and stimulated salivary flow (ESF) 0.98 ± 0,92ml / minute. Hyposalivation occurred in 46.4% of patients; The mean pH 7.39 ± 0.56; 90% in the salivary pH was between 7 and 8. The results show that individuals with CKD have studied satisfactory oral hygiene and low gingival bleeding index, despite the high percentage of dental calculus. Hyposalivation and dry mouth were common conditions as well as increase pH and urea rate in saliva, which averaged 45.31 ± 53.31 mg / dL in the FSR and 47.96 ± 51.86 mg / dL in ESF. Given the results, it is suggested that CKD interfere with salivary composition of hemodialysis patients.